1981
DOI: 10.1530/jrf.0.0610363
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in rete testis fluid secretion and sperm production in different breeds of ram

Abstract: Production of spermatozoa and secretion of rete testis fluid (RTF) in rams was assessed by a rete testis cannulating technique. Four breeds (Ile-de-France, Romanov, Préalpes du Sud and cross-breed Romanov) were studied throughout the year. Inhibitory effects of the cannulation process on spermatogenesis were observed for some animals. Between-breed differences were found in sperm concentration and flow rate of the RTF. The seasonal variations in the daily sperm production of the testis were more pronounced for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 10 publications
1
20
0
1
Order By: Relevance
“…This is an Open Access article, distributed under the terms of the Creative Commons Attribution licence (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted re-use, distribution, and reproduction in any medium, provided the original work is properly cited. doi:10.1017/S1751731117001045 animal and dramatically reduced sperm production in the male (Dacheux et al, 1981). This cycle, modulated by melatonin secretion, is under strong photoperiodic control (Karsch et al, 1984;Malpaux et al, 1997;Thiéry et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This is an Open Access article, distributed under the terms of the Creative Commons Attribution licence (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted re-use, distribution, and reproduction in any medium, provided the original work is properly cited. doi:10.1017/S1751731117001045 animal and dramatically reduced sperm production in the male (Dacheux et al, 1981). This cycle, modulated by melatonin secretion, is under strong photoperiodic control (Karsch et al, 1984;Malpaux et al, 1997;Thiéry et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, spermatogenesis has been shown to change with photoperiod [7, 10, I S]. Seasonal variations in daily sperm production [7] and semen characteristics have also been observed, the best semen generally being obtained in the winter [2,14]. It has been shown that photoperiod has an important effect on production of ejaculated sperm and fertility in rams [3].…”
mentioning
confidence: 99%
“…In addition, feeding and environmental temperature (according to latitude) may modulate photoperiod effects [10,[19][20][21]. Finally, seasonal effects have been shown to differ among breeds [7,17,24,27]. Testosterone was measured by RIA using an anti-T-3-O-carboxymethyloxime-bovine serum albumin antiserum with a previous ether extraction of experimental sera, as described previously [29].…”
mentioning
confidence: 99%
“…Breed differences in susceptibility to photoperiodic changes constitute another source of seasonal variation in sheep reproductive activity. Important differences between breeds have been reported in the timing and magnitude of the seasonal testicular cycle [2], in the seasonal pattern of secretion of gonadotrophins [3,4] and in the seasonality of testicular activity and sperm production [5][6][7][8]. Rams of the "northern breeds" have a marked seasonal reproductive cycle, which is mainly influenced by photoperiodic variation [9].…”
mentioning
confidence: 99%